Pengembangan LKPD berbasis learning cycle 7E pada materi suhu dan kalor - Siti Nurhafiza; Erniwati Halawa (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2026)
AbstractStudents’ low achievement in physics learning is often caused by the use of conventional teaching modules and instructional methods, which tend to make students easily bored and unable to fully understand the material. This condition indicates the need for more innovative learning media that can actively engage students and help them better comprehend the topics being taught. Therefore, this study aimed to develop a Learning Cycle 7E-based Student Worksheet (LKPD) that meets the criteria of validity, practicality, and effectiveness in improving students’ learning outcomes on the topic of temperature and heat. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The trial involved 9 students of class XI-2 for the small-group test and 35 students of class XI-1 for the large-group test, selected through purposive sampling. Data were collected through validation sheets completed by material and media experts, practicality questionnaires from teachers and students, as well as pretests and posttests to measure improvements in learning outcomes. The results showed that the developed LKPD was feasible for use in physics learning. The material expert validation obtained a score of 79% (valid category), while the media expert validation reached 87.5% (very valid category). In terms of practicality, the small-group trial achieved an average score of 76% and the large-group trial achieved 83.1%, both categorized as very practical. Furthermore, there was a significant improvement in students’ learning outcomes, indicated by the increase in the average pretest score from 35.5 to 89.8 in the posttest, with an N-gain score of 0.84 (high category). Thus, the Learning Cycle 7E-based LKPD for the topic of temperature and heat was declared feasible because it was proven to be valid, practical, and effective in supporting physics learning.Keywords: LKPD; learning cycle 7E; ADDIE; temperature and heat; learning outcomesAbstrakRendahnya prestasi belajar fisika siswa seringkali disebabkan oleh penggunaan modul dan metode mengajar yang masih tradisional yang kerap membuat siswa cepat bosan dan sulit memahami materi secara menyeluruh. Kondisi seperti ini menunjukkan bahwa perlu ada alat bantu belajar yang lebih kreatif, agar siswa bisa terlibat aktif dan lebih mudah menyerap setiap topik yang diajarkan. Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis Learning Cycle 7E yang memenuhi kriteria valid, praktis, dan efektif dalam meningkatkan hasil belajar pada materi suhu dan kalor. Metode yang dipakai adalah Research and Development (R&D) dengan model ADDIE, yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Uji coba melibatkan 9 siswa kelas XI-2 untuk kelompok kecil dan 35 siswa kelas XI-1 untuk kelompok besar, yang dipilih secara purposive sampling. Data dikumpulkan melalui lembar validasi oleh ahli materi dan ahli media, angket kepraktisan dari guru dan siswa, serta pretest dan posttest untuk melihat peningkatan hasil belajar. Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan layak digunakan. Penilaian dari ahli materi memperoleh skor 79% (kriteria valid), sedangkan dari ahli media mencapai 87.5% (sangat valid). Dari segi kepraktisan, uji coba kelompok kecil mendapat rata-rata 76% dan kelompok besar 83.1%, keduanya dalam kategori sangat praktis. Selain itu, terjadi peningkatan hasil belajar yang signifikan, ditunjukkan oleh nilai rata-rata pretest 35.5 menjadi 89.8 pada posttest, dengan skor N-gain sebesar 0.84 (kategori tinggi). Dengan demikian, LKPD berbasis Learning Cycle 7E untuk materi suhu dan kalor dinyatakan layak karena terbukti valid, praktis, dan efektif dalam mendukung pembelajaran fisika.Kata kunci: LKPD; learning cycle 7E; ADDIE; suhu dan kalor; hasil belajar